Sports health during the SARS-Cov-2 pandemic - Timpka, T. (Sports Medicine, 2020)
Key Points Sports organisations must adopt pandemic strategies that are unmistakeably communicated to their memberships. Temporary frameworks for sports practices should be developed that harmonise with prevailing social distancing and quarantine regulations. Sports medical researchers and practitioners should cooperate with sports organisations and public health agencies to build trust and resilience and safeguard sports participation at all levels.